Cat Swarm Optimization to Shunt Capacitor Allocation in Algerian Radial Distribution Power System - Amar Hamzi; Rachide Meziane (IAES International Journal of Artificial Intelligence (IJ-AI), 2018)
This paper presents a Cat Swarm Optimization (CSO) Algorithm optimization method to shunt capacitor placement on distribution systems under capacitor switching constraints. The optimum capacitor allocation solution is found for the system of feeders fed through their transformer and not for any individual feeder. The main advantages due to capacitor installation, such as capacity release and reduction of overall power and energy losses are considered. The capacitor allocation constraints due to capacitor-switching transients are taken into account. These constraints are extremely important if pole-mounted capacitors are used together with station capacitor bank. Cat Swarm search algorithm is used as an optimization tool. An illustrative example for Algerian example is presented.